2002
DOI: 10.1034/j.1600-0765.2002.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, immunological and genetic factors in family members with periodontitis as a manifestation of systemic disease, associated with hematological disorders

Abstract: The microflora, immunological profiles of host defence functions, and human leukocyte antigen (HLA) findings are reported for a mother, son and daughter who were diagnosed as having 'periodontitis as a manifestation of systemic diseases, associated with hematological disorders'. Examinations were made of the bacterial flora from the periodontal pocket, neutrophil chemotaxis, neutrophil phagocytosis, and the genotypes (DQB1) and serotypes (DR locus) of HLA class II antigens. Phenotypic analyses of the periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Similar findings have been reported by other investigators (4, 11, 21, 46). In contrast, some studies have not observed any significant difference in PMN phagocytosis between patients with periodontitis and controls (28, 41). Regarding the oxidative burst activity, available data suggest that peripheral PMNs from patients with different forms of periodontitis are ‘hyperactive’, and therefore release greater amounts of lysosomal enzymes and ROS than PMNs from individuals with periodontal health (12, 13, 16, 17, 19, 34, 35).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Similar findings have been reported by other investigators (4, 11, 21, 46). In contrast, some studies have not observed any significant difference in PMN phagocytosis between patients with periodontitis and controls (28, 41). Regarding the oxidative burst activity, available data suggest that peripheral PMNs from patients with different forms of periodontitis are ‘hyperactive’, and therefore release greater amounts of lysosomal enzymes and ROS than PMNs from individuals with periodontal health (12, 13, 16, 17, 19, 34, 35).…”
Section: Discussionmentioning
confidence: 86%
“…It should be pointed out that our main goal in this study was not to evaluate the direct effects of the subgingival microbiota on PMN functions, but rather to determine whether an intrinsic impairment in these cells would be associated with a pathogenic periodontal microbiota and disease. To date, very few studies have correlated the subgingival microbiota with PMN activities in individuals with aggressive disease (28, 36). Moreover, there is not a unique test to measure phagocytic or microbicidal functions of PMNs in the gingival sulcus because a wide variety of subgingival pathogens interact simultaneously with a large number of different components on the surface of these cells, eliciting distinct responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study (44), periodontal therapy seemed to reduce the presence of key pathogens at the site level but failed to confirm the results at the subject level. Although sampling from one site only per subject would provide subject‐based information such processing may not be representative for the subjects (11, 148). It appears that, at the subject level, there are few studies that have presented data on periodontal infection as part of a periodontal diagnosis.…”
Section: Subject‐based Diagnosis Of Periodontitismentioning
confidence: 99%
“…Thus, it seems to be also associated with monocyte deficiency, such as disrupted neutrophil differentiation or chemotaxis. 9 Furthermore, the affected patients have been shown to have inflammatory hyperresponsive phenotype. 10 This genetic predisposition to disease is also found in the expression of major histocompatibility complex, human leukocyte antigen (HLA) genes or cytokines.…”
Section: Introductionmentioning
confidence: 99%